Darkly Perfect World : Colonial Adventure, Postmodernism, and American Noir - Orr, Stanley, 1967- (Book collections on Project MUSE., 2010)
"Stanley Orr’s Darkly Perfect World offers a large-scale historical narrative about the way American crime fiction and film have changed throughout the twentieth century. Orr argues that films noirs and noir fictions dramatize Raymond Chandler’s pronouncement that “Even in death, a man has a right to his own identity.” Orr illuminates a noir ethos committed to “authenticating alienation”: subjectivity managed through radical polarization of Self and Other. Distinguishing a heretofore unrecognized context for American noir, Orr demonstrates that Chandler and Dashiell Hammett arrive at this subject within and against the colonial adventure genre. While the renegades of Joseph Conrad and Louis Becke project a figure vulnerable to shifts in cultural context, the noir protagonist exemplifies alienated selfhood and often performs a “continental operation” against the slippages of the colonial adventurer. But even as Orson Welles, Billy Wilder, and other noir virtuosi persist with this revision of late Victorian adventure, Chester Himes, Dorothy Hughes, and John Okada experiment with hard-boiled alienation for a subversion of noir that resonates throughout literary postmodernism. In their respective avant-garde novels, Thomas Pynchon, Ishmael Reed, and Paul Auster expose what K.W. Jeter terms the “darkly perfect world” of noir, thus giving rise to and enabling the con men and “connected guys” of contemporary films noirs such as Bryan Singer’s The Usual Suspects, David Fincher’s Seven, Christopher Nolan’s Memento, and Quentin Tarantino’s Reservoir Dogs"--Publisher's description.